NILAI KARAKTER PADA BUKU BAHASA INDONESIA SD KELAS V - Arini Widya Safitri; Siti Nurhasanah; Reva Levina Widyadhana; Alfi Khoiru An Nisa (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to identify and describe the character education values contained in the Indonesian Language textbook for Grade V Elementary School using the 2013 Curriculum. The background is the important role of textbooks as a strategic tool in building students’ character. Using a descriptive qualitative approach and content analysis techniques, this study reveals that there are 13 main character values that appear in various story texts in the book. These values include: love of the homeland/national spirit, environmental care, social care, religious, communicative, curiosity, honesty, responsibility, democracy, love of peace, creativity, hard work, and heroic values. These findings indicate that the Indonesian Language textbook for Grade V using the 2013 Curriculum contains various important character values, so that it not only functions as a source of language material, but also as an effective tool to shape students with integrity and responsibility in accordance with national education goals.